Inappropriate dosing of direct oral anticoagulants: findings from a clinical vignette study and physician survey - Ahmet Fuat; Emmanuel Ako; David Hargroves; Douglas Holden; Amrit Caleyachetty; Matthew Carter; James Harris; Carol Roberts; Nnanyelu Nzeakor; Burcu Vardar; Helen Williams (Journal of Market Access & Health Policy)
ABSTRACTObjective Direct oral anticoagulants (DOACs) are first-line therapy for stroke prevention for 1.4 million atrial fibrillation (AF) patients in the UK. However, the rates of DOAC dosing below evidence-based recommendations are estimated between 9% and 22%. This study explores specific patient and physician factors associated with prescribing inappropriate DOAC underdoses.Methods DOAC-prescribing physicians within the UK completed both a clinical vignette survey, which contained 12 hypothetical patient profiles designed to replicate DOAC prescribing scenarios, and a physician survey to capture sociodemographic, clinical experience, and prescriber-related beliefs and motivations related to DOAC prescribing. Eight patient factors based on a literature search and an expert consultation process were varied within the vignettes. Associations between the prescribers’ dosing choices and patient factors were explored via multilevel logistic regression. The analysis is focused on the most frequently selected DOACs, apixaban and rivaroxaban, both of which have different dosing guidelines.Results In all, 336 prescribers (69% male; 233/336) completed the survey, mostly general physicians (GPs) (45%) or cardiology specialists (36%) with a mean of 17.9 years’ experience. Most prescribers (73%; 244/336) inappropriately underdosed at least once; rates between GPs and specialists were nearly identical. Patient factors most strongly associated with apixaban inappropriate underdosing included a history of major bleeding and falls. For rivaroxaban, these were major bleeding and severe frailty. Only 32% (106/335) of prescribers reported DOAC dosing guidelines as the sole influence on their prescribing behaviour. Among prescribers who did not inappropriately underdose, greater prescribing confidence was aligned to increased perception of inappropriate underdose risk.Conclusions Overall, patient factors such as major bleeding and severe frailty were found to be associated with inappropriate underdosing of apixaban and rivaroxaban. Furthermore, prescribers who were more confident in DOAC prescribing, and were more worried about the risk of stroke, were significantly less likely to inappropriately underdose. These findings suggest that all prescribers, regardless of speciality, may benefit from education and training to raise awareness of the risks associated with inappropriate DOAC underdosing.